Weight-Adjusted Waist Index, Psoriasis, and All-Cause Mortality: Findings from the NHANES 2003–2006 and 2009–2014 - Zhou T; Wu J; Wang Y; Gao Y; Cheng K (Clinical, Cosmetic and Investigational Dermatology)
Tianjing Zhou, Jianming Wu, Yingwei Wang, Yu Gao, Kai Cheng Department of Dermatology, The Second School of Medicine, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, People’s Republic of ChinaCorrespondence: Kai Cheng, The Second Affiliated Hospital and Yuying Children’s Hospital of Wenzhou Medical University, 109 Xue Yuan West Road, Wenzhou, Zhejiang, 325000, People’s Republic of China, Email chengkai202409@163.comPurpose: Psoriasis is associated with obesity, which in turn is linked to increased mortality risk. Therefore, we undertook a cohort study utilizing data from the National Health and Nutrition Examination Survey (NHANES) to examine the impact of weight-adjusted waist index (WWI) on the likelihood of all-cause mortality in psoriasis individuals.Patients and Methods: This study utilized data from the National Health and Nutrition Examination Survey (NHANES) to investigate the influence of WWI on the probability of all-cause mortality in psoriasis individuals. A retrospective cohort analysis included 19,919 participants aged 18 to 80 years, with or without psoriasis. The primary endpoint studied was all-encompassing mortality up to December 2019. The interplay between WWI and psoriasis was analyzed through multivariable logistic regression techniques. Survival probabilities were assessed employing Kaplan-Meier curves and Cox regression analyses.Results: Out of the 19,919 subjects that we eventually included, 522 had psoriasis. Psoriasis and WWI were found to be significantly positively correlated. A significant correlation was found between an incremental unit increase in WWI and a 63% increased risk of all-cause mortality risk in psoriasis patients (HR = 1.63, 95% CI 1.02– 2.61). Subgroup analyses demonstrated consistent findings within the psoriasis population. These findings suggest an independent impact of WWI on psoriasis risk and mortality.Conclusion: Our investigation revealed that there is a strong positive correlation between WWI and all-cause mortality in US psoriasis adults. For those with psoriasis, managing WWI, or obesity, is crucial.Keywords: psoriasis, obesity, WWI, all-cause mortality, NHANES